PROBLEMS OF THE FORMATION OF UNIVERSAL AND PROFESSIONAL COMPETENCES IN THE FSES HE 3 ++ AND THE WAYS OF THEIR SOLUTIONS - I. N. Mishin (Высшее образование в России)
А critical assessment of the content of the new educational standards (FSES HE 3 ++), developed on the basis of application of professional standards, is carried out in the article. The author determines the problems related to the content of universal competencies (UC), the formation of a list of professional competencies (ProfC), and outlines the ways to solve the identified problems. The author emphasizes attention on the incorrect formulations of individual UC, on the lack of normative base for the formation of a list of ProfC based analytical data. The author criticizes the system of independent qualification exams and proposes the revision of the FSES HE 3 ++, and of the regulatory base of higher education, the increase in the variability of educational programs, creating a list of compulsory innovative ProfC, the optimization of the organization of educational process in the conditions of the real production to improve the efficiency of professional training of graduates at universities.